Role modelling in medical education: the importance of teaching skills. (28th June 2015) - Burgess, Annette; Oates, Kim; Goulston, Kerry
Summary: Objectives: By observation of role models, and participation in activities, students develop their attitudes, values and professional competencies. Literature suggests that clinical skills and knowledge, personality, and teaching skills are three main areas that students consider central to the identification of positive role models. The aim of this study was to explore junior medical students' opinions of the ideal attributes of a good role model in clinical tutors. Methods: The study was conducted with one cohort ( n = 301) of students who had completed year 1 of the medical programme in 2013. All students were asked to complete a questionnaire regarding the ideal attributes of a good role model in a clinical tutor. The questionnaire consisted of seven closed items and one open‐ended question. Results: The response rate to the questionnaire was 265/301 (88%). Although students found all three key areas important in a good role model, students emphasised the importance of excellence in teaching skills. Specifically, students see good role models as being able to provide a constructive learning environment, a good understanding of the curriculum and an ability to cater to the learning needs of all students. Students see good role models as being able to provide a constructive learning environment Conclusion: While acknowledging the importance of a patient‐centred approach, as well as clinical knowledge and skills, our findings reinforce the importance of the actual teaching abilities of role models within medical education.